Quality of life and physical activity in an older working-age population - Puciato, Daniel; Borysiuk, Zbigniew; Rozpara, Michał (Clinical interventions in aging, 2017)
Physical activity can be an effective means of prevention and therapy of many psychosomatic disorders. It can also have a significant impact on the quality of life of older working-age people. The aim of the present study was to assess the relationships between quality of life and physical activity in older working-age people from Wrocław, Poland. The study group comprised 1,013 people, including 565 women and 448 men, aged 55-64 years (59.1±2.9 years). The study took form of a questionnaire survey. The participants assessed their physical activity and quality of life using the International Physical Activity Questionnaire Short Version (IPAQ-SF) and the World Health Organization Quality of Life (WHOQOL-BREF), respectively. The highest mean indices of general quality of life, perceived health status, and quality of life in the physical, psychological, social, and environmental domains were shown by respondents whose intensity of physical activity was the highest. Moreover, the odds of high assessment of overall quality of life increased with respondents' higher levels of physical activity. Quality of life improvement programs should also involve increased physical activity components.